DYNAMICS OF INTERNATIONAL INVESTMENT FLOWS AND THEIR IMPLICATIONS FOR INDONESIA’S ECONOMIC SOVEREIGNTY - Riady Ibnu Khaldun (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores international investment flows and their influence on Indonesia’s economic sovereignty in the era of globalization. The main goal is to analyze how foreign direct investment (FDI) affects national economic resilience, especially regarding policy independence and strategic development priorities. The research uses a descriptive qualitative approach with secondary data from international financial institutions and national economic reports, covering the period 2019–2023. The findings show that foreign investment brings major benefits, such as boosting economic growth, enabling technology transfer, and creating jobs. However, it also creates risks of dependency and limits Indonesia’s ability to make independent policies. In addition, global economic competition and regional integration frameworks shape the movement of capital and domestic policy responses. The study highlights the need for a balanced strategy: maximizing the benefits of foreign investment while protecting long-term economic sovereignty through strong regulations, selective sector priorities, and closer regional cooperation. In conclusion, sustainable sovereignty requires not only attracting investment but also strengthening institutions and ensuring consistent policies so that external capital supports rather than undermines national development goals